Obtenção de fotocatalisadores magnéticos a partir de resíduos industriais e TiO2 para a degradação de contaminantes orgânicos - Pereira, Leydiane de Oliveira (2016)
In this work, magnetic photocatalysts were synthesized containing differents levels of TiO2 (40, 60 e 80%) supported at the supporter of C/LV, forming the photocatalysts 40, 60, 80Ti/C/LV, using tar pitch as carbon (C) source and red mud (LV) as iron source. The prepared magnetic photocatalysts and TiO2 were used to degrade the Remazol Black textile dye (PR5) and the organic material present in samples of a textile dye effluent. The characterization of photocatalysts by Raman, X-Ray Diffraction, Transmission Electron Micoscope and Scanning, Energy Dispersive X-ray Spectrometry, Termogravimetry and Elemental Analysis, confirms the presence of carbon and magnetite in support C/LV and the presence of TiO2 in prepared photocatalysts. The photocatalytic reactions with TiO2 were analyzed by different experimental conditions, such as: mass of TiO2 (30-240 mg), solution pH (2-10), light intensity (0.871 and 1.20 mWcm-2), type of radiation (UV and sunlight-1.420 mWcm-2), radiation incidence area (44.2 to 143.1 cm2) and dissolved oxygen (OD, 1.9 and 7.6 mg L- 1). Results showed that reactions with the following conditions: 220 mg of TiO2, pH 10, solar radiation, 7.6 mg L-1 of OD and an incidence area of radiation of 143.1 cm2 showed the best results for degradation of PR5 dye. Photocatalytic reactions with magnetic photocatalysts for degrading PR5 shows that efficiency increases with TiO2 content in the C/LV support, where, above 60% of TiO2, there was not significant increase in reaction velocity. In addition, solar radiation has proved to be advantageous for photocatalytic reactions. In order to verify the presence of a non-magnetic fraction in the photocatalyst 60Ti/C/LV0, magnetic separation was proceeded. The characterizations of the magnetic (FM) and nonmagnetic (NMF) fraction confirmed that about 25% of TiO2 did not fixed in 60Ti/C/LV photocatalyst. Results of photocatalytic reactions with FM and FNM showed that both phases have photocatalytic activity for degradation of PR5. The reactions executed for the degradation of organic matter present in the actual sample of textile effluent showed that TiO2 and magnetic photocatalyst 60Ti/C/ LV have better results for color removal (85 to 35%), soluble solids ( 11 and 3%), DQO (90 and 86%) and turbidity (94 and 11%) than the treatment done by the textile industry. Sedimentation kinetics tests in presence of a magnet showed that photocatalysts are separated faster from aqueous environment than pure TiO2. Obtained results showed that magnetic photocatalysts have excellent photocatalytic activity and can be separated from the reaction environment on a simple and quick way when a magnetic field is applied.